Model Perilaku Konsumtif Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Swasta Di Kota Medan - Mukmin Pohan; Muhammad Elfi Azhar; Nadia Ika Purnama; Hanifah Jasin (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to study the factors that influence the Consumptive Behavior of Students and produce a Model of Consumptive Behavior of Students of the Development Economics Study Program, Faculty of Economics and Business, Private University in Medan City. This research is a basic research (basic research). The population in this study were all students of the Development Economics Study Program, Faculty of Economics and Business, Private University in Medan City. Sampling in this study used purposive sampling with the criteria of students of the Development Economics Study Program in semester IV and VI. The determination of the number of samples in this study is based on the Central Limit Theorem which states that the number of samples to achieve the normal curve is at least 30 respondents. The reason for determining the number of samples using the Central Limit Theorem is because the total population in this study is unknown. A total of 150 questionnaires were sent so that respondents who returned the questionnaires were expected to be at least 30 students. Data collection techniques used are interviews (interviews), list of questions (questionaire) and study documentation. The data analysis method used is descriptive analysis and multiple linear regression. The results showed that there was a significant effect of Lifestyle on Consumption Behavior, there was a significant influence of Financial Literacy on Consumption Behavior. There is a significant effect of Financial Literacy on Consumption Behavior which is moderated by Religiousity and there is no significant effect of the moderating effect of Religion on the relationship between Lifestyle and Consumption Behavior.